1999
DOI: 10.3109/10799899909036637
|View full text |Cite
|
Sign up to set email alerts
|

Extracts and Constituents ofHypericum PerforatumInhibit the Binding of Various Ligands to Recombinant Receptors Expressed with the Semliki Forest Virus System

Abstract: Extracts, fractions and constituents of Hypericum perforatum were studied for in vitro receptor binding with various ligands to recombinant CNS receptors expressed with the Semliki Forest virus expression system. For this purpose we have prepared membranes of CHO cells with high density of several opioid, serotonin, estrogen, histamine, GABAA, neurokinin and metabotropic glutamate receptors, respectively. A lipophilic Hypericum fraction revealed relatively potent inhibition to the binding of the mu-, delta- an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
38
0
3

Year Published

1999
1999
2007
2007

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(43 citation statements)
references
References 20 publications
2
38
0
3
Order By: Relevance
“…The phloroglucinol derivative hyperforin has recently become a molecule of increasing interest. Studies have demonstrated significant effects of hyperforin on various serotonergic, noradrenergic, dopaminergic, cholinergic, and opioid system activities in vitro (Chatterjee et al, 1998a;Holcomb et al, 1982;Müller et al, 1998Müller et al, , 2001Neary et al, 2001;Simmen et al, 1999;Singer et al, 1999;Wonnemann et al, 2001). As the in vitro data have been used to argue that hyperforin is the major active principle of SJW extract, we determined in the present study whether it is active in vivo in a model of therapeutic efficacy.…”
Section: Introductionmentioning
confidence: 88%
See 3 more Smart Citations
“…The phloroglucinol derivative hyperforin has recently become a molecule of increasing interest. Studies have demonstrated significant effects of hyperforin on various serotonergic, noradrenergic, dopaminergic, cholinergic, and opioid system activities in vitro (Chatterjee et al, 1998a;Holcomb et al, 1982;Müller et al, 1998Müller et al, , 2001Neary et al, 2001;Simmen et al, 1999;Singer et al, 1999;Wonnemann et al, 2001). As the in vitro data have been used to argue that hyperforin is the major active principle of SJW extract, we determined in the present study whether it is active in vivo in a model of therapeutic efficacy.…”
Section: Introductionmentioning
confidence: 88%
“…The pharmacological activity of SJW extracts has recently been reviewed (Butterweck, 2003;Greeson et al, 2001;Nathan, 1999). Reports about the antidepressant activity of SJW extracts and their constituents both in vivo and in vitro have been published (Baureithel et al, 1997;Butterweck et al, 1997Butterweck et al, , 1998Butterweck et al, , 2000Butterweck et al, , 2001aButterweck et al, , b, 2002Calapai et al, 1999;Chatterjee et al, 1996Chatterjee et al, , 1998aDi Matteo et al, 2000;Franklin and Cowen, 2001;Gobbi et al, 1999Gobbi et al, , 2001Müller et al, 1997Müller et al, , 1998Müller et al, , 2001Simmen et al, 1999Simmen et al, , 2001Singer et al, 1999;Wonnemann et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Test compounds were first assayed at 10 μM for intrinsic activity (agonist or inverse agonist) using the [ 35 4) at room temperature for 1 h, after which bound radioligand was separated from free via rapid vacuum filtration over GF-B filters with a Brandel Scientific (Gaithersburg, MD) 96-well harvester. Bound radioactivity was determined using a TopCount 12-detector instrument (Packard Instruments) using standard scintillation counting techniques.…”
Section: Intrinsic Activity At Human Opioid Receptorsmentioning
confidence: 99%